Design and Development of a Microcontroller based Egg Incubator for Small Scale Poultry Production (Global Journal of Science Frontier Research, 2016)
A study was conducted to design and develop a microcontroller baser egg incubator for small scale poultry production. The incubator was equipped with microcontrollers to control the egg turner, heater, and circulation fan. It was designed to operate at average temperature of 38C. The turner operates at 10 cycles per minute for 30 seconds every 6 hours while the circulation fan activates every hour for 30 seconds to circulate the air inside the incubator. The prototype incubator was tested by loading it with 20 pieces of chicken eggs from a breeding flock. It was found that the prototype incubator functioned as designed during the entire incubation period. Two eggs were hatched after 21 days of incubation and another egg was hatched on the 24 th day of incubation period. The percent egg fertility was found to be 55% or 11/20 while the hatchability was only 27% or 3 out of 11 fertile eggs. The low hatchability of fertile eggs could be more likely attributed to frequent power outage of 2 to 6 hours a day during the entire incubation period. A stable and uninterrupted power supply is needed for the optimal hatching performance of the incubator.
Keywords: microcontroller; incubator; temperature sensor; relay driver; relay; heater and buzzer